111 New normal ranges and superior reproducibility of 3d myocardial strain on cardiovascular magnetic resonance-feature tracking. (5th June 2017) - Liu, Boyang; Sinha, Ayushka; Moody, William; Leyva, Francisco; Edwards, Nicola; Steeds, Richard
Abstract : Background: Myocardial deformation can be key to clinical decision. 2D feature-tracking of cardiovascular magnetic resonance (CMR-FT) imaging is user-friendly but has poor reproducibility, particularly for radial strain. 3D CMR-FT may improve repeatability by reducing through-plane artefact. The aim of this study was to provide normal ranges for 3D CMR-FT and compare its reproducibility to older generation 2D CMR-FT. Method: 56 asymptomatic, healthy subjects (43.7±12.9 year, 52% male) undertook CMR (1.5 Tesla scanner Magnetom Avanto, Siemens, Erlangen, Germany). 3D FT-CMT was generated using the SSFP HLA, VLA and short axis cine images (Figure 1). A single observer (BL) analysed the CMR studies using 2D and 3D CMR-FT (Circle cvi 42 ® version 5.3) and after 4 weeks, re-analysed blinded scans for intra-observer variability. Inter-observer variability was generated by separate tracking by a second blinded observer (AS) in a randomly generated subset of 15 subjects. Agreement was tested by calculating mean bias and 95% limits of agreement (confidence intervals) from Bland–Altman analyses, coefficient of variation, and inter-class correlation coefficient (ICC). Results: There is modest agreement between all measures of 2D and 3D peak strain analysis (ICC=0.44 to 0.58). Mean global circumferential strain (GCS) on 3D analysis is −16.8±2.5, compared to 2D GCS of −20.2±3.31 and −20.6±3.4 at the base and mid-ventricular level respectively. Mean global longitudinal strain (GLS) is −13.7±2.3 on 3D CMT-FT and −19.3±2.7 on 2D CMR-FT. Global radial strain (GRS) is 45.5±10.9 for 3D, compared to 55.1±14.4 and 48.0±13.4 at the base and mid-ventricular level respectively. Table 1 displays the inter- and intra-observer variability of each technique. Intra-observer variability was significantly improved by 3D CMT-FT for GCS, whilst inter-observer variability was significantly improved for GCS, GRS and strain rates. No reproducibility differences were identified for GLS. Discussion: Peak strains using 3D FT-CMR is different to 2D normal range values. 3D CMR-FT has superior intra- and inter-observer reproducibility compared with 2D CMR-FT, particularly for GCS and GRS strain, the latter being the principal systolic strain and should improve detection of sub-clinical ventricular dysfunction.